Chronic exposure to manganese sulfate leads to adverse dose‐dependent effects on the neurobehavioral ability of rats. Issue 11 (19th June 2015) - Su, Cheng; Chen, Kangcheng; Zou, Yunfeng; Shen, Yuefei; Xia, Bing; Liang, Guiqiang; Lv, Yingnan; Wang, Fenfen; Huang, Damin; Yang, Xiaobo
ABSTRACT: Manganese sulfate is the main combustion product of methylcyclopentadienyl manganese tricarbonyl (MMT). Currently, little is known about the neurobehavioral consequences of chronic manganese sulfate exposure. In this study, rats were treated with 0, 5.0, 10.0, and 20.0 mg/kg MnSO4 ·H2 O for 24 consecutive weeks via intraperitoneal injection. During the treatment period, spatial learning‐memory ability was measured using the Morris water maze (MWM). At the end of the exposure period, spontaneous motor behavior and emotional status, hippocampal histologic changes, and Hsp70 mRNA levels were measured using the open‐field test (OFT), hematoxylin‐eosin staining and real‐time quantitative PCR (RT‐PCR), respectively. A dose‐dependent decrease was noted in the spatial learning‐memory ability and the spontaneous activities of rats ( P  < 0.05), and negative emotions differed significantly between the exposed groups and the control group ( P  < 0.05). Moreover, overt morphological changes in the hippocampuses of the exposed rats were detected. Cellular degeneration and death were also found. The Hsp70 mRNA levels of the hippocampal areas in the 20.0 mg/kg group (1.567 ± 0.236) were significantly increased compared with the control group ( P  < 0.05). These results suggest that chronic exposure to manganese sulfate can have adverse dose‐dependent effects on rats' neurobehavioral ability, and the mechanism of abnormal hippocampal Hsp70 expression needs to be further explored. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1571–1579, 2016.